ANALISA STABILITAS DINDING PENAHAN TANAH PADA KEGIATAN PEMBANGUNAN JALAN POROS TRANS KALIMANTAN STA 08 + 470 KABUPATEN KUTAI BARAT - ABIDIN, ZAINAL (KURVA S JURNAL MAHASISWA, 2018)
The presence of several landslide points on the trans Kalimantan has caused the transportation facilities to be slightly obstructed, and the risk of interruption of roads which can cripple transportation facilities. to realize safe, comfortable, and durable construction on the slope area, an analysis of the level of slope security in its planning is needed. The level of safety of a slope is influenced by several factors, including the slope factor and the load acting on it. Slope conditions with large loads and steep slopes can cause landslides. Building slope reinforcement construction, Soil strengthening on slopes that is often used as a solution to avoid landslides is the construction of retaining walls. In general there are several methods in analyzing slope stability, in this case the author uses the rankine and coulomb methods to calculate the soil support stability and active and passive soil pressure. because this method can be applied to land with geographical conditions on the island of Kalimantan which has many steep cliffs and cliffs.